Stakeholders' Perceptions on Earnings Management Motivations and Techniques in Libyan Commercial Banks - Yasser Barghathi (Journal of Accounting and Management Information Systems (JAMIS), 2017)
The issue of earnings management has continued to be problematic in the financial reporting context. It has proved to be an important topic that concerns a wide range of stakeholders including regulators, investors and preparers. This paper examines the perceptions of Libyan Commercial Banks' (LCBs) stakeholders regarding earnings management (EM) motivations and techniques. The paper reports on a questionnaire survey of stakeholders which yielded 102 Responses (response rate 53%). It is found that LCBs' managers are engaged in EM practices as a result of a number of motivations. In consistent with accounting literature on EM, LCBs' managers tend to use Loan Loss Provision LLP as well as other techniques to manage their earnings. However, the research finding reveal some other "techniques" that are being used for EM. Some of them clearly lay out of GAAP and law framework which may be seen as an explicit breach to bank managers' accountability. The importance of the banking sector for society has been amply demonstrated in recent years. The evidence provided by the questionnaire results refer to a serious problem to the accountability of LCBs' managers. The existence of these motivations, which appear to be unavoidable, put pressure on the accountability process and expose it to a lack of trust and disrepute which therefore may have an adverse effect on the relationship between LCBs' managers and their stakeholders. LCBs' manager should be free from such motivations in order to produce unbiased and fair accounting information.
Keywords: M41; 650; earnings management; EM motivations; EM techniques; stakeholders; banks; perceptions